2017
DOI: 10.1038/nrn.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in neurodegeneration

Abstract: The emerging complexity of the transcriptional landscape poses great challenges to our conventional preconceptions of how the genome regulates brain function and dysfunction. Non-protein-coding RNAs (ncRNAs) confer a high level of intricate and dynamic regulation of various molecular processes in the CNS and they have been implicated in neurodevelopment and brain ageing, as well as in synapse function and cognitive performance, in both health and disease. ncRNA-mediated processes may be involved in various asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(113 citation statements)
references
References 247 publications
(226 reference statements)
0
112
0
1
Order By: Relevance
“…The magnitude of interactions shown by network analyses, further complicated by high between-tissue variability, presents one of today's largest obstacles in microRNA (miRNA) research. Because miRNAs exert individual effects of low impact, the outcome of their cooperative action can be more adequately represented by a network approach than by traditional molecular interaction studies (Salta and De Strooper, 2017). Although experimental validations are necessary, they often significantly exceed the scope of scientific publications, even for one single miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of interactions shown by network analyses, further complicated by high between-tissue variability, presents one of today's largest obstacles in microRNA (miRNA) research. Because miRNAs exert individual effects of low impact, the outcome of their cooperative action can be more adequately represented by a network approach than by traditional molecular interaction studies (Salta and De Strooper, 2017). Although experimental validations are necessary, they often significantly exceed the scope of scientific publications, even for one single miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of interactions shown by network analyses, further complicated by high betweentissue variability, presents one of today's largest obstacles in microRNA research. As miRs exert individual effects of low impact, the outcome of their cooperative action can be more adequately represented by a network approach than by traditional molecular interaction studies (Salta and De Strooper, 2017). While experimental validations are necessary, they often significantly exceed the scope of scientific publications even for one single miR.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptic or skiptic DNA elements may be associated with disease in humans but not exist in mice, such as the cryptic polyadenylation site in STATHMIN2 (a neuronal growth associated factor) that is present in sporadic and some genetic forms of ALS (26) . Non-coding changes also modulate disease outcomes: for example, by 2017 more than 3,000 different genome-wide association studies (GWAS) had reported >30,000 SNP-disease associations, the vast majority of which lie in non-coding regions (27), indicating the importance of gene regulation in disease, including neurodegenerative disease (25,28).…”
Section: Mice and Humans Are Differentmentioning
confidence: 99%